Associations between job burnout and self-efficacy: a meta-analysis. Issue 4 (3rd July 2016) - Shoji, Kotaro; Cieslak, Roman; Smoktunowicz, Ewelina; Rogala, Anna; Benight, Charles C.; Luszczynska, Aleksandra
ABSTRACT: Background and Objectives : This study aimed at systematically reviewing and meta-analyzing the strength of associations between self-efficacy and job burnout (the global index and its components). We investigated whether these associations would be moderated by: (a) the type of measurement of burnout and self-efficacy, (b) the type of occupation, (c) the number of years of work experience and age, and (d) culture.Design and Methods : We systematically reviewed and analyzed 57 original studies ( N = 22, 773) conducted among teachers ( k = 29), health-care providers ( k = 17), and other professionals ( k = 11).Results : The average effect size estimate for the association between self-efficacy and burnout was of medium size (−.33). Regarding the three burnout components, the largest estimate of the average effect (−.49) was found for the lack of accomplishment. The estimates of the average effect were similar, regardless of the type of measures of burnout and self-efficacy measurement (general vs. context-specific). Significantly larger estimates of the average effects were found among teachers (compared to health-care providers), older workers, and those with longer work experience.Conclusions : Significant self-efficacy–burnout relationships were observed across countries, although the strength of associations varied across burnout components, participants' profession, and their age.